MEASURING PARENT–CHILD MUTUALITY: A REVIEW OF CURRENT OBSERVATIONAL CODING SYSTEMS - Funamoto, Allyson; Rinaldi, Christina M. (Infant mental health journal, 2015)
ABSTRACT Mutuality is defined as a smooth, back‐and‐forth positive interaction consisting of mutual enjoyment, cooperation, and responsiveness. The bidirectional nature of mutuality is an essential component to the parent–child relationship since a high quality parent–child mutual relationship is crucial to encouraging children's positive socialization and development (S. Lollis & L. Kuczynski, 1997; E.E. Maccoby, 2007). Several coding systems have been developed in recent years to assess this distinct and crucial aspect of the parent–child relationship. The present article reviews the following four mutuality coding schemes: the Parent–Child Interaction System (K. Deater‐Deckard, M.V. Pylas, & S. Petrill, 1997), the Mutually Responsive Orientation Scale (N. Aksan, G. Kochanska, & M.R. Ortmann, 2006), the Caregiver‐Child Affect, Responsiveness, and Engagement Scale (C.S. Tamis‐LeMonda, P. Ahuja, B. Hannibal, J.D. Shannon, & M. Spellmann, 2002), and the Synchrony and Control Coding Scheme (J. Mize & G.S. Pettit, 1997). The review will focus on observational coding schemes available to researchers interested a central element of quality parent–child relationships in the early years. RESUMEN La mutualidad se define como una delicada, positivamente cambiante interacción, conformada por una mutua satisfacción, cooperación y capacidad de respuesta. La naturaleza bidireccional de la mutualidad es un componente esencial en la relación entre progenitor y niño, ya que una mutua relación de alta calidad entre progenitor y niño es crucial para alentar la positiva socialización y desarrollo de los niños (Lollis y Kuczynski, 1997; Maccoby, 2007). En años recientes, se han desarrollado varios sistemas de codificación con el fin de evaluar este singular y crucial aspecto de la relación entre progenitor y niño. El presente estudio revisa los siguientes cuatro esquemas de codificación de la mutualidad: el Sistema de Interacción Progenitor‐Niño (PARCHISY; Deater‐Deckard, Pylas, Petrill, 1997), la Escala de Orientación de la Recíproca Capacidad de Respuesta (MRO; Aksan, Kochanska y Ortmann, 2006), la Escala de Afecto, Capacidad de Respuesta e Involucramiento del Niño y el Cuidador (C‐CARES; Tamis‐LeMonda, Ahuja, Hannibal, Shannon y Spellmann, 2002) y el Esquema de Codificación de Sincronía y Control (Mize y Pettit, 1997). La revisión se enfocará en los esquemas de codificación por medio de la observación disponibles para los investigadores interesados en un elemento central de la calidad de las relaciones progenitor‐niño en los primeros años. RÉSUMÉ La mutualité est définie comme une interaction douce, allant et venant, positive consistant en un plaisir mutuel, une coopération et une réaction. La nature bidirectionnelle de la mutualité est une composante essentielle à la relation parent‐enfant, étant donné qu'une relation mutuelle de haute qualité est crucial pour l'encouragement de la socialisation positive des enfants et de leur développement (Lollis & Kuczynski, 1997; Maccoby, 2007). Plusieurs systèmes de codage ont été développés ces dernières années de façon à évaluer cet aspect distinct et crucial de la relation parent‐enfant. Cet article passe en revue les quatre projets de codage de mutualité suivants: Système d'Interaction Parent‐Enfant, en anglais Parent‐Child Interaction System (PARCHISY; Deater‐Deckard, Pylas, & Petrill, 1997), l'Echelle d'Orientation Mutuellement Réactive, en anglais Mutually Responsive Orientation Scale (MRO; Aksan, Kochanska, & Ortmann, 2006), les Echelles C‐CARES, en anglais Caregiver‐Child Affect, Responsiveness, and Engagement Scale (C‐CARES; Tamis‐LeMonda, Ahuja, Hannibal, Shannon, & Spellmann, 2002), et le Plan de Codage de Contrôle et de Synchronie, en anglais Synchrony and Control Coding Scheme (Mize & Pettit, 1997). L'article mettra l'accent sur les plans de codages observationnels à la disposition des chercheurs intéressés par l’élément central des relations de qualité parent‐enfant ces dernières années. ZUSAMMENFASSUNG Gegenseitigkeit ist als ausgeglichene, beidseitig positive Interaktion, bestehend aus gegenseitiger Freude, Kooperation und Responsivität definiert. Die bidirektionale Natur der Gegenseitigkeit ist ein wesentlicher Bestandteil der Eltern‐Kind‐Beziehung, da eine hohe Qualität der wechselseitigen Eltern‐Kind‐Beziehung wichtig ist, um die positive Sozialisation und Entwicklung der Kinder zu fördern (Lollis & Kuczynski, 1997; Maccoby, 2007). Mehrere Kodierungssysteme wurden in den letzten Jahren entwickelt, um diesen eigenständigen und wichtigen Aspekt der Eltern‐Kind‐Beziehung zu beurteilen. Der vorliegende Artikel liefert einen Überblick über die folgenden vier Kodierungsschemata zur Gegenseitigkeit: das Parent‐Child Interaction System (PARCHISY; Deater‐Deckard, Pylas, & Petrill, 1997), die Mutually Responsive Orientation Scale (MRO; Aksan, Kochanska, & Ortmann, 2006), die Caregiver‐Child Affect, Responsiveness, and Engagement Scale (C‐CARES; Tamis‐LeMonda, Ahuja, Hannibal, Shannon, & Spellmann, 2002), und die Synchrony and Control Coding Scheme (Mize & Pettit, 1997). Das Review fokussiert auf beobachtungsbasierte Kodierungsschemata, die Forscher nutzen können, wenn sie an einem zentralen Element der Qualität von Eltern‐Kind‐Beziehungen in den ersten Jahren interessiert sind. ABSTRACT 抄録：相互性mutualityは、相互の喜び、協働、および応答性を構成している、なめらかな、行ったり来たりの、ポジティブな相互交流と定義される。相互性の二方向性という性質は、親子関係性の本質的な構成要素である。というのは、高品質な親子の相互関係性は、子どものポジティブな社会化と発達を促進するからである(Lollis & Kuczynski, 1997; Maccoby, 2007)。近年、この親子関係性のはっきりとしていてきわめて重大な面を評価するために、いくつかのコード化システムが開発されてきた。この論文では、以下の４つの相互性をコード化する図式をレビューした。それらは、Parent‐Child Interaction System (PARCHISY; Deater‐Deckard, Pylas, & Petrill, 1997)、Mutually Responsive Orientation Scale (MRO; Aksan, Kochanska, & Ortmann, 2006)、Caregiver‐Child Affect, Responsiveness, and Engagement Scale (C‐CARES; Tamis‐LeMonda, Ahuja, Hannibal, Shannon, & Spellmann, 2002)、そしてthe Synchrony and Control Coding Scheme (Mize & Pettit, 1997)である。レビューは、早期の質の高い親子関係性の中心的な要素に興味を持っている研究者に利用可能な、観察によるコード化図式に焦点を当てるだろう。 摘要 相互關係被定義為以共同享受，合作和共鳴去構成圓滑和雙向的良性互動關係。在親子關係中，相互關係的雙向性是一個重要部分，因為高品質的親子互動關係對鼓勵兒童的良性社會化和發展是非常重要（Lollis & Kuczynski, 1997; Maccoby, 2007）。近年發展了一些編碼系統以評估這親子關係中獨特和重要的一面。本文綜述了以下四個相互關係的編碼方案：親子互動系統（PARCHISY; Deater‐Deckard, Pylas, & Petrill, 1997），相互回應取向量表（MRO; Aksan, Kochanska, & Ortmann, 2006），照顧者‐兒童的情感，響應度和投入量表（C‐CARES; Tamis‐LeMonda, Ahuja, Hannibal, Shannon, & Spellmann, 2002），以及同步性和控制編碼方案（Mize & Pettit, 1997）。本綜述將集中於給對這早年品質親子關係的核心要素有興趣的研究人員提供可用的觀察性編碼方案。